Show that, for all a, b and c, a^log_b (c) = c^log_b (a).

We want to prove:

    alogb(c) = clogb(a).

Recall that we can always write x = eln(x), so xy = (eln(x))y = ey ln(x).

Recall also the change of basis formula for logs:

logb (x) = y  <=>  by = x  <=>  y ln(b) = ln(x)  <=>  y = logb(x) = ln(x) / ln(b).

Putting these two remarks together, we have:

    alogb(c) = elogb(c) ln(a) = e[ln(c) / ln(b)] ln(a) = e[ln(a) / ln(b)] ln(c) = elogb(c) ln(a) = clogb (a).

Q.E.D.

Answered by Tutor69809 D. Maths tutor

5078 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the integral I of e^(2x)*cos*(x), with respect to x


How can functions be transformed?


I'm supposed to calculate the differential of f(x)= sin(x)*ln(x)*(x-4)^2 using the product rule. I know what the product rule is but I can't split this into two bits that are easy to differentiate. How do I do it?


How do you take the derivative of a^x ?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences